Пам'ятні дати: Блумздей Джеймса Джойса та трагедія Ірландії в «Уліссі» - Сафіюк, О. (Літературознавчі обрії. Праці молодих учених, 2010)
The article reveals the origin of Bloomsday and James Joyce’s becoming a writer. The tragedy of Ireland in «Ulysses» shows not only the despair of its nation, but also the indifference to the development of its culture and gaining the independence. Through the formula «internal world – a man – Ireland – the world» the writer shows hopeless position of the Irish people and Ireland itself.